The theory of vibronic transitions in rare earth compounds - Malta, O. L. [UNESP] (Elsevier, 1995)
The theory of vibronic transitions in rare earth compounds is re-examined in the light of a more reliable representation for the ligand field Hamiltonian than the crude electrostatic model. General expressions that take into account the relevant contributions from the forced electric dipole and dynamic coupling mechanisms are derived for the vibronic intensity parameters. These include additional terms, from charge and polarizability gradients, which have not been considered in previous work. Emphasis is given to the relative signs of these various contributions. Under certain approximations these expressions may be conveniently written in terms of accessible ligand field parameters. A comparison with experimental values for the compounds Cs2NaEuCl6 and LiEuF4 is made and satisfactory agreement between theory and experiment is found. A discussion is given on the sensitivity of the calculated intensities to the values of radial integrals, interconfigurational energy differences and ligand field parameters that may be used. Finally, the problem in which a vibronic and an electronic level are in resonance, or near resonance, is analyzed. Suitable expressions to describe the effects of the even-rank components of the vibronic Hamiltonian are obtained. It is found that, depending on the strength of the vibronic interaction and the resonance conditions, the admixture between these two levels may lead to intensities of nearly equal values. © 1995.